Increased risk of hepatitis B virus reactivation in systemic lupus erythematosus patients receiving immunosuppressants: a retrospective cohort study. (January 2018) - Lin, W T; Chen, Y M; Chen, D Y; Lan, J L; Chang, C S; Yeh, H Z; Yang, S S
Objective: We aimed to investigate risk of hepatitis B virus reactivation in systemic lupus erythematosus patients with different hepatitis B virus infection statuses receiving immunosuppressive therapy. Methods: We retrospectively analyzed systemic lupus erythematosus patients with positive hepatitis B surface antigen or anti-hepatitis B core IgG antibody who underwent immunosuppressive therapies from January 2001 to December 2012 at a medical center in Taiwan for evidence of hepatitis B virus reactivation. Results: During this period, 906 out of 3125 patients who were diagnosed with systemic lupus erythematosus received screening tests for hepatitis B virus. Thirty-eight patients were identified as hepatitis B surface antigen-positive. Fifteen of 38 (39.5%) hepatitis B surface antigen-positive patients developed hepatitis B virus reactivation, and 53.3% of these patients experienced severe hepatitis flare. Three of 157 hepatitis B surface antigen-negative/anti-hepatitis B core IgG antibody-positive patients (1.9%) experienced hepatitis B surface antigen seroreversion after immunosuppressive therapy. Five patients received prophylactic or preemptive antiviral therapy and none of them developed hepatitis B virus flares. A daily dose of prednisolone greater than 5 mg was a risk factor for hepatitis B reactivation by multivariate logistic analysis. Conclusions: The risk of hepatitis B virus reactivation is high in lupus patients receiving immunosuppressive therapy. Antiviral prophylaxis or preemption can effectively reduce the incidence of hepatitis B virus reactivation in lupus patients.